Salt-related knowledge, attitudes and practices and their relationship with 24-h urinary sodium and potassium excretions among a group of healthy residents in the UAE: a cross-sectional study - Amjad H Jarrar; Pariyarath S Thondre; Leila Cheikh Ismail; Helen Lightowler; Mo'ath F Bataineh; Alia K Al Baloushi; Amira Y Al Braiki; Shaima Al Halabi; Joudi Hajouz; Usama Souka; Fatima Al Meqbaali; Lily Stojanovska; et al. (Cambridge University Press, 2024)
Abstract Objective: This study aimed to measure urinary sodium and potassium as a measure of sodium and potassium intake concerning the knowledge, attitude and practice towards sodium intake among a group of healthy residents in the UAE. Design: A cross-sectional study on a sample of healthy adults in the UAE. In addition to the knowledge, attitude and practice questionnaire, sodium and potassium excretions and food records were taken. Setting: The UAE. Participants: A sample of 190 healthy individuals aged between 20 and 60 years. Results: The mean (± s d) age of the sample was 38·6 (± 12·5) years, and 50·5 % were females. The mean urinary sodium and potassium intake were 2816·2 ± 675·7 mg/d and 2533·3 ± 615 mg/d, respectively. The means were significantly different compared with the WHO recommendation of sodium and potassium (P < 0·001). About 65 % of the participants exceeded the WHO recommendations for salt intake, and participants' knowledge classification for health-related issues was fair, while food-related knowledge was poor (P = 0·001). A two-stage stepwise multiple regression analysis revealed that knowledge, attitude and practice scores were negatively associated with urinary sodium excretion (r = -0·174; P = 0·017) and those older participants and females had lower urinary sodium excretion (P < 0·001). Conclusions: These findings may suggest an increase in the risk of hypertension in the UAE population. Moreover, these findings emphasise the need to establish education and public awareness programmes focusing on identifying the sodium contents of foods and establishing national regulations regarding food reformulation, particularly for staple foods such as bread.